Shaping ability and cyclic fatigue resistance between Genius ProFlex, ZenFlex, and TruNatomy rotary systems: an experimental study - Raimundo Sales de Oliveira Neto; Murilo Priori Alcalde; Pedro Cesar Gomes Titato; Pedro Henrique Souza Calefi; Carlos Alberto Spironelli Ramos; Guilherme Ferreira da Silva; Rodrigo Ricci Vivan; Marco Antonio Hungaro Duarte (Restorative Dentistry & Endodontics, 2025)
Objectives The aim of this study was to investigate the efficacy of three newly introduced rotary endodontic systems: Genius ProFlex (Medidenta), TruNatomy (Dentsply Maillefer), and ZenFlex (Kerr). Methods Forty-five mandibular molars with root canal curvatures <5° were utilized. Micro-computed tomography scans were performed pre- and post-preparation to assess apical transportation, centralization, percentage of dentin wear, and canal volume alterations. Eight instruments of each diameter underwent cyclic fatigue testing. Results The percentage of dentin wear on mesial and distal walls showed no significant differences among ZenFlex, TruNatomy, and Genius ProFlex at 1, 2, 3, and 4 mm from the apical foramen and root canal orifice (p > 0.05). Centering ability varied in the mesiolingual canal (p < 0.05). No notable differences were observed in transportation (p > 0.05). Genius ProFlex demonstrated lower volumetric changes (p < 0.05). There were significant differences in cyclic fatigue, with higher values for Genius ProFlex and lower values for TruNatomy (p < 0.05). Conclusions The three nickel-titanium rotary instruments are safe and efficient for root canal preparation, with Genius ProFlex exhibiting superior cyclic fatigue resistance.